The importance of using molecular techniques in laboratory diagnosis of Dengue virus: a review (Research, Society and Development, 2021)
Arboviruses correspond to diseases transmitted to humans by the bite of arthropod vectors and constitute a growing public health problem. Most of these arboviruses are emerging and circulating throughout the country, among them, the dengue virus stands out. This arbovirus has four serotypes, DENV1-4, so it is important to use techniques that can identify the present serotype. In this context, this study is a literature review that aims to demonstrate the importance of using molecular techniques in the diagnosis of dengue. To this end, searches were performed for scientific articles in the PubMed, LILACS, SciElo and Academic Google databases. It was found that the use of the molecular technique of RT-PCR and its variations are highly important for viral detection, as well as for the differentiation of circulating serotypes. Therefore, this is a technique that has advantages in diagnosing dengue, as it has good sensitivity, specificity and reproducibility. Therefore, it is observed that laboratory molecular diagnosis contributes positively to viral isolation, in addition to ensuring the identification of the circulating genotype and thus guaranteeing which serotype prevails in a given location. These isolation advantages contribute to epidemiological control and serve to alert health authorities to promote preventive and control measures for this disease.